Computer-assisted image processing technique for tracking wound progress - Haider, Ali; Alhashim, Minhal; Tavakolian, Kouhyar; Fazel-Rezai, Reza (IEEE International Conference on Electro Information Technology, 2016)
The purpose of this study was to develop an algorithm to support the decisions of expert physicians in the management of wound healing. The goal was to work towards the development of an image processing algorithm for quantifying the progress of healing of skin wounds. For this algorithm development, multiple wound images were obtained from patients in clinical settings to monitor the status of wound healing after excision of skin lesions. Dermatologists applied Vaseline and novel experimental natural ointment (NENO) at two different spots on the same subject. The developed algorithm was evaluated for its compatibility to monitor the healing as well as a potential tool to compare the efficacy of Vaseline and NENO to heal the wound. Skin color was used as a feature to measure wound progress. Based on the temporal change of the skin color, decisions were made on whether the wound is healing or expanding. The proposed processing technique was able to detect the color change within the range of 10% to 90%.